STRATEGI GURU PJOK MENINGKATKAN MINAT SISWA DALAM OLAHRAGA DI SMP - Syahrianursaifi, Syahrianursaifi; Noor, Mohd Zairul Mohd; Is, Zulheri; Musran, Musran; Kurniawan, Erizal; Safrizal, Safrizal (Jurnal Dedikasi Pendidikan, 2023)
Strategies to Increase Children's Interest in Sports and Physical Activity are important issues in the world of health and education. Exercise and physical activity are essential to children's growth and health, but often their interest in them is low. The study aims to analyze the factors influencing a child's interest in physical activity and sports and provide strategies to increase their interest. The results of the study show that the environment, education, and the role of parents have a great influence on children's interest in physical activity and sports. Increasing students' interest in sports in junior high schools is an important goal for PJOK teachers. This can help students develop physical fitness, mental health, and essential skills such as teamwork and discipline. Therefore, PJOK teachers can apply several strategies, such as creating a fun and positive atmosphere, providing various types of sports, involving students in the learning process, using technology, creating competitive sports activities, and giving rewards or rewards. By implementing this strategy, it is hoped that students will be more motivated to participate in sports activities and develop important skills. In order to increase students' interest in sports in junior high schools, PJOK teachers need to make constant efforts to improve the quality of learning and create a conducive environment for students to participate in sports activities